When the “Weight” of the Philological Research may turn into Burden (I): que + Vowel in the Galician-Portuguese Secular Lyrical Poetry - Fernández Guiadanes, Antonio (Madrygal. Revista de Estudios Gallegos, 2017)
Nobiling and Cunha’s studies stated that in the Galician-Portuguese secular lyrical poetry the intervocabular union between the conjunction or the pronoun que and a vowel (accented or unaccented) was resolved on hiatus. Later, M. Ferreiro highlighted that, in many editions, scholars often did not consider this rule while establishing the critical text of the cantigas they were editing. In this contribution we intend to review the approaches to the edition of some verses that these researchers proposed in their studies, in order to restore the isometry that Michaëlis and Lang (respectively, in the Cancioneiro da Ajuda and Don Denis’ Cancioneiro editions) resolved through synalepha. We will also discuss cases in which we disagree with most editors or that we think that still deserve some reflection.